A Analisis Tempat Penampungan Sementara (TPS) Menggunakan Sistem Informasi Geografis Untuk Pengelolaan Sampah Berkelanjutan di Kota Lhokseumawe - Abbas, Rahmat; Cut Ayu Lizar; Satriawan, Halus (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), Politeknik Negeri Cilacap, 2025)
Lhokseumawe City is the center of government and economy has a dense population, with a population density index of 1,082.6 people / km2. Good waste management must be done to maintain environmental health, including the management of Temporary Shelters (TPS). Waste that is disposed of carelessly creates illegal Waste Disposal Sites (LPS) that can trigger various diseases and reduce environmental aesthetics. The focus of the research is to map the location of TPS and LPS using Geographic Information System (GIS), analyze the distribution pattern of TPS and LPS using nearest neighbor analysis on image processing software, and analyze the suitability of TPS capacity with the volume of waste from the people of Lhokseumawe City. The results of the study obtained that the TPS facilities in Lhokseumawe City are 18 TPS while there are 36 illegal LPS. The distribution pattern of TPS includes a clustered pattern with a distribution index of 0.69. The distribution pattern of LPS includes a clustered pattern with a distribution index of 0.51 and the highest LPS is found in the Muara Satu District area. The results of the analysis of the suitability of TPS capacity obtained the availability of TPS in each sub-district is still lacking to accommodate waste generation, Banda Sakti sub-district still lacks 34 TPS, Muara Dua sub-district 23 TPS, Muara Satu sub-district 15 TPS, and Blang Mangat sub-district 8 TPS.. Keywords: TPS, Geographic Information System, Waste, Nearest Neighbor, Mapping